2023
DOI: 10.1002/pmic.202200242
|View full text |Cite
|
Sign up to set email alerts
|

Applying single‐cell highly multiplexed secretome proteomics to characterize immunotherapeutic products and predict clinical responses

Abstract: Genetically and phenotypically identical immune cell populations can be highly heterogenous in terms of their immune functions and protein secretion profiles. The microfluidic chip-based single-cell highly multiplexed secretome proteomics enables characterization of cellular heterogeneity of immune responses at different cellular and molecular layers. Increasing evidence has demonstrated that polyfunctional T cells that simultaneously produce 2+ proteins per cell at the single-cell level are key effector cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 133 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…When compared to flow cytometry, it was shown that chipbased cytometry offers a significantly increased sensitivity and a specificity of a similar level [60]. This approach may be also of a high diagnostic value since it can provide the detection and phenotyping of rare cell subsets in precious, small clinical samples [60,64,65]. IsoLight is also a new system that detects the secreted proteins from single cells based on single-cell barcode chip technology [66].…”
Section: Emerging Single-cell Proteome Analysis Technologiesmentioning
confidence: 99%
“…When compared to flow cytometry, it was shown that chipbased cytometry offers a significantly increased sensitivity and a specificity of a similar level [60]. This approach may be also of a high diagnostic value since it can provide the detection and phenotyping of rare cell subsets in precious, small clinical samples [60,64,65]. IsoLight is also a new system that detects the secreted proteins from single cells based on single-cell barcode chip technology [66].…”
Section: Emerging Single-cell Proteome Analysis Technologiesmentioning
confidence: 99%